Brain metabolic alterations in patients with long‐term calcineurin inhibitor therapy after liver transplantation. Issue 11 (21st April 2019) - Schmitz, Birte; Pflugrad, Henning; Tryc, Anita B.; Lanfermann, Heinrich; Jäckel, Elmar; Schrem, Harald; Beneke, Jan; Barg‐Hock, Hannelore; Klempnauer, Jürgen; Weissenborn, Karin; Ding, Xiao‐Qi
Summary: Background: Calcineurin inhibitor (CNI) neurotoxicity after liver transplantation might be due to impairment of the cerebral metabolism. Aims: To investigate CNI‐related alterations of brain metabolite distributions and associations between cognitive function and brain metabolism in patients with long‐term CNI treatment after liver transplantation. Methods: Eighty‐two patients (19 CNI free, 34 CNI low‐dose and 29 standard‐dose CNI immunosuppression) 10 years after liver transplantation and 32 adjusted healthy controls underwent nonlocalised brain phosphorus magnetic resonance spectroscopy (MRS) and single voxel proton MRS in the parietal white matter to estimate brain metabolite contents. The MRS results were correlated with psychometric data assessing cognitive function. Results: Phosphorus metabolite concentrations with the exception of phosphocreatine (PCr) were reduced in patients compared to controls. Particularly, patients with low‐dose CNI therapy showed a significant decrease in adenosine triphosphate (0.209 ± 0.012 vs 0.222 ± 0.010; P  < 0.001) and a significant increase in PCr (0.344 ± 0.026 vs 0.321 ± 0.017; P  < 0.001) compared to controls. Myo‐Inositol in the CNI free group (2.719 ± 0.549 institutional unit [iu]) was significantly lower compared to controls (3.181 ± 0.425 iu; P  = 0.02), patients on low‐dose (3.130 ± 0.513 iu; P  < 0.05) and standard‐dose CNI therapy (3.207 ± 0.632 iu; P  < 0.02). Glutamate and glutamine levels correlated negatively with cognitive function (Repeatable Battery for the Assessment of Neuropsychological Status Total Scale: R  = −0.362, P  = 0.029). Conclusion: Long‐term CNI therapy after liver transplantation might be associated with alterations of brain metabolites.